Structural integrity of liner cement in oil & gas wells: Parametric study, sensitivity analysis, and risk assessment. (April 2021) - Patel, Harshkumar; Salehi, Saeed
Highlights: Influence of material properties on cement integrity in oil & gas wells. Effect of cement column length in liner-casing overlap. Influence of annulus pressure on cement top failure. Sensitivity analysis of stresses in cement. Risk assessment and identification of likely failure modes in shallow liner cement. Abstract: Cement is an important barrier element that provides pressure isolation between formation(s) and a well. Failure in the cement sheath can compromise well integrity and potentially lead to severe environmental, health, safety, and business impacts. This work aims to assess fitness-for-service of cement sheath specifically in the context of shallow depth liner-casing overlaps in offshore wells. Primary objective of this paper is to investigate influence of pressure loads, material properties, and sheath dimensions on structural integrity of cement. The ultimate objective is to perform risk assessment and identify likely modes of failure. This work is based on a three-dimensional finite element model of cement sheath validated by analytical calculations. Sensitivity analysis was performed to evaluate and rank the influence of various operating and design parameters on mechanical stresses in a cement sheath. Results indicate that cement material properties (Young's modulus, Poisson's ratio, expansion) and wellbore pressure are the major factors influencing cement's structural integrity. Risk assessment suggests that interfacial bond failure, radial cracking, and cement top failure are likely modes of structural failure for a cement sheath in shallow-depth liner-casing overlap. Flexible and expanding cement are likely to be more robust to structural failure than brittle and non-expanding cement. Although annulus pressure has negligible influence on stress distribution within bulk of a cement sheath, it can potentially cause failure near the top of the cement column. Sensitivity curves generated in this work will help engineers understand performance of cement sheath under different conditions. Regulators and industry will be able to strengthen the guidelines for assessment and qualification of cement as a barrier.